2023
DOI: 10.1021/acsami.3c01145
|View full text |Cite
|
Sign up to set email alerts
|

Brightening up Full-Color and White Circularly Polarized Luminescence through Chiral Induction and Circularly Polarized Light Excitation

Abstract: Preparation of chiral materials from achiral helical polymers has aroused great interest among researchers. In this work, chiral small molecules were utilized to accomplish chiral induction toward racemic helical polyacetylene via intermolecular π–π stacking by which chiral films with strong optical activity were fabricated. Furthermore, introducing fluorescent components generated full-color and white circularly polarized luminescence (CPL). A CPL generation mechanism is proposed accordingly, namely circularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 62 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…The dynamic chirality inversion of these coassemblies can be also achieved by tuning the assembling temperature, since the assembly pathways are highly dependent on the temperature and play important roles in the supramolecular chirality regulation of the resultant assemblies. , As shown in Figure S37, the CD spectra of PVPCC/Zn­(NO 3 ) 2 /dyes showed obviously negative CD absorptions with broad shoulder peaks (corresponding to the UV absorption of the doping dyes) at 298 K, indicating the effective chirality transfer in the resultant aggregates. By contrast, negative CD peaks below 400 nm (assigned to the CD absorption of PVPCC/Zn­(NO 3 ) 2 aggregates) and inwardly convergent curves above 400 nm (assigned to the CD absorption of the dye-based aggregates) were observed in the aggregates of PVPCC/Zn­(NO 3 ) 2 /dyes at 273 K. The result suggested that the different dye stacking occurred in the aggregates processed at different assembling temperature. This temperature-directed aggregation of dyes was clearly demonstrated by the CPL investigation.…”
Section: Resultsmentioning
confidence: 95%
“…The dynamic chirality inversion of these coassemblies can be also achieved by tuning the assembling temperature, since the assembly pathways are highly dependent on the temperature and play important roles in the supramolecular chirality regulation of the resultant assemblies. , As shown in Figure S37, the CD spectra of PVPCC/Zn­(NO 3 ) 2 /dyes showed obviously negative CD absorptions with broad shoulder peaks (corresponding to the UV absorption of the doping dyes) at 298 K, indicating the effective chirality transfer in the resultant aggregates. By contrast, negative CD peaks below 400 nm (assigned to the CD absorption of PVPCC/Zn­(NO 3 ) 2 aggregates) and inwardly convergent curves above 400 nm (assigned to the CD absorption of the dye-based aggregates) were observed in the aggregates of PVPCC/Zn­(NO 3 ) 2 /dyes at 273 K. The result suggested that the different dye stacking occurred in the aggregates processed at different assembling temperature. This temperature-directed aggregation of dyes was clearly demonstrated by the CPL investigation.…”
Section: Resultsmentioning
confidence: 95%
“…4 To more clearly demonstrate the CPF-ET process, recently, we obtained full-color and white CPL by taking advantage of circularly polarized light excitation (CP-Ex) as well as chiral induction strategy. 29 In the presence of a PMMA matrix, through intermolecular π−π stacking interactions, the chirality of α-pinene was transferred to racemic helical polyacetylene (PMY), resulting in the formation of chiral solid film (Figure 8a). Then, four achiral fluorophores were introduced into the chiral films to fabricate CPL-active blend films.…”
Section: Circularly Polarized Fluorescence Energy Transfermentioning
confidence: 99%
“…A series of CPL materials were obtained using this method, including metal complexes, , organic small molecules, π-conjugated polymers, and so forth. In addition, CPL materials can also be obtained by introducing chiral dopants or chiral environment into achiral luminescent materials through physical doping method. Regardless of the method used to prepare CPL materials, the chiral arrangement of chromophores is the key to achieving CPL.…”
Section: Introductionmentioning
confidence: 99%